A Patient-derived Constant-Murley Score is Comparable to a Clinician-derived Score - Levy, Ofer (Springer US, 2013)
BACKGROUND: Although there are many advantages to patient-based assessment for musculoskeletal conditions, one common problem is that many of these assessments are perceived to be subjective. To overcome this limitation for patient-based shoulder evaluation, we developed a modified Constant-Murley score that allows patients to complete subjective and objective sections of the score. QUESTIONS/PURPOSES: The purpose of our study was to assess the reliability of the new patient-based Constant-Murley score questionnaire by comparing composite scores and subscores obtained with those obtained using the standard physician-based Constant-Murley questionnaire in the same group of patients. METHODS: Between August and October 2000, all patients having shoulder surgery in our institute were invited to participate in this study; 58 of 61 (95%) opted to do so and completed the patient-based questionnaire at preoperative and postoperative assessments. The clinician-based Constant-Murley score was performed by a clinician who was blinded to the corresponding patient-based questionnaire. Patients underwent various procedures ranging from manipulation under anesthesia and arthroscopic procedures to reverse shoulder arthroplasty. RESULTS: The mean patient-based and the clinician-based Constant-Murley scores were 47 (SD = 19.5; range, 4–90; N = 108) and 48 (SD = 19.9; range, 4–90; N = 108) points respectively. The mean difference was −1.3 (SD = 3; range, −11 to 8; N = 108) points. The new patient-based Constant-Murley score questionnaire reproduced the patient-based method and had substantial to almost perfect agreement with it for the composite score and various subgroups. CONCLUSIONS: These results suggest that a patient-based questionnaire can be used interchangeably with or in place of a clinician-based Constant-Murley score. These results apply to subjective and objective items of the Constant-Murley score. LEVEL OF EVIDENCE: Level III, diagnostic study. See the Instructions for Authors for a complete description of levels of evidence.